Flipped Classroom in the Context of Higher Education: Learning, Satisfaction and Interaction - María José Sosa Díaz; Jorge Guerra Antequera; Mario Cerezo Pizarro (MDPI AG, 2021)
Educational governmental institutions have recommended implementing blended learning in higher education to respond to the "new educational normality" caused by the COVID-19 pandemic, although this is not a new challenge. Over the last few decades, higher education institutions have tried to incorporate the use of technological devices to university teaching, by redesigning and optimizing the learning experiences through a mixed teaching model. In this context, the Flipped Classroom (FC) model is one of the pedagogical models that is revolutionizing the scope of education. However, there is still not enough evidence of its advantages and disadvantages in the university stage. Therefore, it is important to analyze the impact of the FC on the learning, satisfaction and interaction of the different agents of the university community. Due to the idiosyncrasy of the present study, an exclusively qualitative and longitudinal methodology was selected; thus, 266 interviews based on open questions were conducted throughout the last five years. The results show that students value the FC model positively and corroborate its great potential from academic, competence, personal and social perspectives. Nevertheless, a small group of students are still very critical about the model and would prefer to keep using a traditional methodology, mainly due to the lack of habit using active methodologies and establishing the learning commitment required by such methodologies.